Determination of Suitable Transport Layers in Light of Interface Defect States in MASnX3‐Based Perovskite Solar Cell. Issue 11 (30th August 2022) - Mottakin, Muhammad; Sobayel, Khan; Ismail, Rizalafande Che; Shahiduzzaman, Md.; Muhammad, Ghulam; Ibrahim, Mohd Adib; Akhtaruzzaman, Md.; Hossain, Erajder Sabbir
Abstract : Interface defects are crucial to improve the perovskite solar cell stability. This study investigates and determines the suitable electron transport layer (ETL) for Sn‐based perovskite solar cells. The investigation finds that carriers capture cross‐sectional area greatly impacts photovoltaic performance, and the optimum value is 1 × 10 −25 cm 2 . A low trap density of 10 12 cm − 2 does not play a significant role, but an interface defect density of 10 17 cm − 2 located near the valence band edge at the ETL/absorber interface has the most detrimental effect. In structure, defect states ( E t ) near the valence band edge of PCBM/CH3 NH3 SnI3 /NiO and WO3 /CH3 NH3 SnI3 /NiO devices have a higher destructive impact compared to TiO2 /CH3 NH3 SnI3 /NiO. The study also finds that absorber bulk defects and the interface defects in the ETL/absorber layer are the most sensitive to device performance. This detrimental impact on cell performance can be avoided by reducing the capture cross‐sectional area and maintaining a low trap density. Abstract : This study investigates and determines the suitable electron transport layer based on interface defect for Sn‐based perovskite solar cells. Defect states near the valence band edge and midbandgap energy have a higher destructive impact than the conduction band edge. It is possible to prevent this detrimental impact by reducing the capture cross‐sectional area and maintaining a low trap density.